Fashion franchises - Review of Croatia and North Macedonia - Aleksandar Erceg; Vera Boškovska; Liljana Kukec (UTMS Journal of Economics, 2023)
Franchising is one of the most used strategies and/or modes for growing and expanding business as franchisors and starting new ventures as franchisees from the other side. Franchising is used for growing and expanding business not only in domestic but also in the international market. It can be seen in many industrial sectors, production companies, and service-providing companies. In the fashion and retail sectors, franchising is deeply embedded and represents one of the most obvious answers and one of the best strategies for expansion. Over the last several years, we have witnessed the expansion of different fashion brands in the region through franchising, especially their international expansion. Thus, we have investigated the situation in the fashion industry, especially the brands that use franchising as their primary growth strategy. The paper's primary goal is to analyze fashion franchising as a potential growth model for domestic fashion companies. Paper analyses and presents results of franchising in the world fashion industry and examines the situation in Croatia and North Macedonia. As a research result, it is seen that fashion franchising is mainly presented through international companies and that there are only rare examples of domestic fashion companies that franchise.
Keywords: M19; M21; 330; fashion industry; franchising; Croatia; North Macedonia; similarities; differences